Fatigue evaluation by using microcomputer-based acceleration data logger for swimming research - Ohgi, Y.; Ichikawa, H. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION The underwater videography has several difficulties in its process. Especially, the three dimensional analysis for swimmer's stroke evaluation takes much time and work. Therefore it is not suitable feedback method at the poolside coaching. The authors put our hopes on the tiny acceleration sensors and microcomputer. Purpose of this study was to develope an acceleration sensor device which can obtain swimmer's wrist acceleration. Then, we applied this device for the swimmer's fatigue evaluation by the acceleration data. METHODS Two bi-axial monolithic acceleration sensor IC(ADXL210, Analog Devices Inc.,) were built in aluminium alloy cylinder. Thus, we could measure tri-axial acceleraion simultaneously. A microcomputer which had CPU, Memory, A/D converter and I/O functions was also built in it. This device functions under 200m depth over a half and an hour with 128Hz sampling rate. The subjects swam intensive interval training with crawl stroke. The swimmer's strokes were monitored by the computer controled underwater pan-tilt cameras which were also developed for our experiment. The joints' coordinates of upper extremity were reconstructed by DLT method. We attached the device on the subject's left wrist. We examined the relationships between the change of the swimmer's wrist acceleration and the stroke paths with training intensity. Connecting the sensor device with PC by paralell cable, we could download the stored acceleration data. RESULTS X-axis and Z-axis accelerations showed impact peak at the entry moments. Therefore, we could extract every single stroke acceleration. This means that we can obtain precise stroke rate of each stroke. The Y-axis acceleration which was along with longitudinal axis of the forearm changed with the training intensity. The local maximum which appeared after the global maximum during single stroke decreased by swimmer's fatigue. This local maximum corresponded with the beginning of the upsweep phase. The angular velocity of the elbow joint at that time also decreased by swimmer's fatigue. DISCUSSION Since the experimental stroke style was crawl stroke, the centrifugal acceleration was likely to be a major component of the wrist acceleration during swimmer's arm rotation movement. Although swimmer's stroke rate had increased at the fatigue situation, the Y-axis acceleration decreased relatively. At the upsweep phase, he finished his underwater stroke with his elbow keeping bend. According to the angle and the angular velocity of elbow joint, the subject could not extend maximaly by his exhaustion. The evidence that the change of his stroke with fatigue could be observed in the wrist accelerations.